Gross, Background, and Net Anthropogenic Soil Nitrous Oxide Emissions from Soybean, Corn, and Wheat Croplands. Issue 1 (1st January 2019) - Della Chiesa, Tomas; Piñeiro, Gervasio; Yahdjian, Laura
Abstract : Agricultural soils are the largest single source of N2 O emissions globally. However, soils left uncultivated would still release N2 O. Distinguishing anthropogenic from natural emissions (i.e., background emissions) in crops is important if we want to assess the net effect of human activity. This study aimed to characterize N2 O emissions from croplands and unmanaged grasslands to estimate the net anthropogenic emissions and to gain a better insight into their main drivers. We established a replicated manipulative field experiment in the Pampas Region of Argentina to quantify soil N2 O emissions from corn ( Zea mays L.), wheat ( Triticum aestivum L.), and soybean [ Glycine max (L.) Merr.] crops, and from adjacent unmanaged grassland plots for 1 yr. We also analyzed the main controls of N2 O emissions and the correlation between the normalized difference vegetation index (NDVI) and N2 O fluxes. Background emissions represented between 21 and 32% of total emissions from croplands, depending on crop type. No differences were detected in N2 O emissions between total and background during winter and peak crop growing season. NDVI showed a significant correlation with N2 O fluxes which was positive in grasslands and negative in growing season of soybean crops. Our results showed that N2 O emissions from croplands were higher than background emissions, but also that background represented an important fraction of cropland emissions. Higher emissions in croplands occurred during pre‐seeding, after harvest, and after N fertilization in fertilized crops. In addition, our study informs about N2 O emissions from crops and unmanaged systems in South America where field data are very scarce. Core Ideas: We measured soil N2 O emissions in South America where field data are very scarce. Nonanthropogenic fluxes represented 21 to 32% of crop N2 O emissions. NDVI, a plant productivity index, improved seasonal estimation of N2 O flux.